2019
DOI: 10.1002/ajhb.23339
|View full text |Cite
|
Sign up to set email alerts
|

The Xavante Longitudinal Health Study in Brazil: Objectives, design, and key results

Abstract: Objective The Xavante Longitudinal Health Study was developed to permit granular tracking of contemporary health challenges faced by indigenous communities in Brazil, taking into consideration ongoing historical processes that may be associated with increases in child undernutrition, adult obesity, and cardiovascular disease risks. Methods This was an open‐cohort study with six semiannual data collection waves from 2009 to 2012. The study was undertaken in two Xavante villages, Pimentel Barbosa and Etênhiritip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 42 publications
2
13
0
3
Order By: Relevance
“…In Brazil, a socio-epidemiological longitudinal study found marked disparities in the double burden of malnutrition (including anemia and excess weight) of the indigenous populations compared to the general population (Welch et al 2020). In cross-sectional studies, the double burden of malnutrition (stunting in children and excess weight in the mother) was associated with the educational level and nonmasonry (inadequate) houses (Gea-Horta et al 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Brazil, a socio-epidemiological longitudinal study found marked disparities in the double burden of malnutrition (including anemia and excess weight) of the indigenous populations compared to the general population (Welch et al 2020). In cross-sectional studies, the double burden of malnutrition (stunting in children and excess weight in the mother) was associated with the educational level and nonmasonry (inadequate) houses (Gea-Horta et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies focused on indigenous populations (Coimbra et al 2013;Ramirez-Zea et al 2014;Welch et al 2020;Ramírez-Luzuriaga et al 2020). Welch et al (2020) found that, in children under ten years old in indigenous communities in Brazil, stunting, wasting, and malnutrition, including anemia, were more notorious.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 The Xavante indigenous people are recognized as one of the ethnic groups with diverse reports and studies in the fields of anthropology, demography and health, in particular the population of the indigenous land (IL) Pimentel Barbosa, which has investigations carried out since the 1950s, being accompanied through studies in the same fields mentioned until the present moment. [7][8][9][10][11] Based on the results of the 2000 Census, observed for the Xavante population of six IL, compared to the same data from a second source (Indigenous Health Information System -SIASI (Sistema de Informação a Saúde Indígena)), the authors considered the population size and its distribution in age groups and sex to be consistent, being located primarily in indigenous reserves, in the rural area of the encompassing municipalities. 9,12 The Xavante's demographic dynamics involve recognized population growth in contexts of high infant mortality rates.…”
Section: Sociodemographic Characteristics Related To Xavante's Healthmentioning
confidence: 99%
“…In relation to waist circumference, the Munduruku presented a lower mean [85.3 cm (±10.2)], when compared to the Xavante indigenous people (Mato Grosso) [95.1 (±8.3) [34], but higher when compared to the Yanomami (Roraima) [76.3 (±46.8)] [35].…”
Section: Plos Onementioning
confidence: 99%